An alarming tendency towards freshwater mussel misidentification in scientific works may bias endangered and invasive species management - Bolotov, Ivan N.; Konopleva, Ekaterina S.; Vikhrev, Ilya V.; Kondakov, Alexander V. (Aquatic conservation, 2024)
Freshwater mussels (order Unionida) are a popular group for a wide array of non‐taxonomic research driven by questions related to their functions in ecosystems, to relationships among species, to biogeochemical and morphometric patterns of certain species and others. Valid taxonomy and correct species identification are key requirements for all of these aspects. However, species‐level identification of representatives from this group is a rather complicated task and should be based on an integrative approach, combining DNA sequences, morphological and anatomical investigation and biogeographical estimates. This article reconsiders a selection of non‐taxonomic scientific works (N = 25), containing misidentified occurrences of freshwater mussel species. The dataset contains records of the endangered Margaritifera margaritifera (endemic to eastern North America and Europe) from the Philippines and West Africa, as well as occurrences of the Nearctic Gonidea angulata from West Africa and the Middle East. Several Palearctic and Nearctic unionid species were erroneously reported from the Indus River, Pakistan. Subfossil shells of the native Simpsonella sp. from a prehistoric site in the Philippines were misidentified as the invasive Sinanodonta woodiana that was introduced to the islands in the 20th century. Samples of the tropical lineage of S. woodiana from Indonesia were mistaken for the native Pilsbryoconcha exilis, and vice versa. Salinity tolerance and morphometric characteristics of the estuarine clam Geloina sp. (Cyrenidae) from Sumatra were examined, but these data were published as belonging to the strictly freshwater S. woodiana. It is clear that this information, being reused by researchers, conservationists and stakeholders, will lead to incorrect conclusions on the range, status, biogeochemistry, morphometry and ecological tolerance of certain freshwater mussel taxa, including invasive and endangered species (the so‐called ‘error cascades’ in biological sciences caused by ‘bad taxonomy’). To reduce the growing body of literature containing misidentifications of the Unionida taxa, practical recommendations are proposed for researchers, who include freshwater mussels in non‐taxonomic surveys, as well as for journal editors dealing with articles that focus on these animals.